2015
DOI: 10.1186/s12977-015-0231-z
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral DNA—the silent winner: blood transfusion containing latent feline leukemia provirus causes infection and disease in naïve recipient cats

Abstract: Background The feline leukemia virus (FeLV) is a gamma-retrovirus of domestic cats that was discovered half a century ago. Cats that are infected with FeLV may develop a progressive infection resulting in persistent viremia, immunodeficiency, tumors, anemia and death. A significant number of cats mount a protective immune response that suppresses viremia; these cats develop a regressive infection characterized by the absence of viral replication and the presence of low levels of proviral DNA. The biological im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 64 publications
1
41
0
3
Order By: Relevance
“…14,39 For more detail about other diagnostic methods of FeLV detection, including virus isolation, immunofluorescence for detection of FeLV cell-associated p27 antigen in circulating leukocytes and platelets, and most recently a laboratory-based ELISA to detect p27 antigen (PetChek FeLV 15™), we refer to studies published elsewhere. 49 Although immunofluorescence testing is still recommended as the confirmatory test of choice for FeLV diagnosis in North America, 16 PCR testing is now recommended as the confirmatory test of choice for FeLV diagnosis in Europe 7 and studies evaluating the performance of FeLV PoC test kits using PCR as the confirmatory test are becoming more common. However, one important advantage of PCR testing over all other currently available diagnostic methodologies is its ability to detect regressive FeLV infections.…”
Section: Felv Diagnosis Using Whole Blood and Poc Antigen Test Kitsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,39 For more detail about other diagnostic methods of FeLV detection, including virus isolation, immunofluorescence for detection of FeLV cell-associated p27 antigen in circulating leukocytes and platelets, and most recently a laboratory-based ELISA to detect p27 antigen (PetChek FeLV 15™), we refer to studies published elsewhere. 49 Although immunofluorescence testing is still recommended as the confirmatory test of choice for FeLV diagnosis in North America, 16 PCR testing is now recommended as the confirmatory test of choice for FeLV diagnosis in Europe 7 and studies evaluating the performance of FeLV PoC test kits using PCR as the confirmatory test are becoming more common. However, one important advantage of PCR testing over all other currently available diagnostic methodologies is its ability to detect regressive FeLV infections.…”
Section: Felv Diagnosis Using Whole Blood and Poc Antigen Test Kitsmentioning
confidence: 99%
“…47,48 Alarmingly, a recent study demonstrated the ability of regressively infected cats to cause progressive infections in naïve cats following a blood transfusion, highlighting the need to screen potential blood donors for regressive FeLV infection with PCR testing prior to transfusion instead of relying solely performing PoC testing. 49 Although immunofluorescence testing is still recommended as the confirmatory test of choice for FeLV diagnosis in North America, 16 PCR testing is now recommended as the confirmatory test of choice for FeLV diagnosis in Europe 7 and studies evaluating the performance of FeLV PoC test kits using PCR as the confirmatory test are becoming more common. 14,39 We evaluated the performance of three FeLV PoC test kits commercially available in Australia (the same three brands used for FIV testing, i.e.…”
Section: Felv Diagnosis Using Whole Blood and Poc Antigen Test Kitsmentioning
confidence: 99%
“…Fifty days prior to plasma transfusion and experimental infection, the SPF status of all the cats was confirmed by testing for the absence of infection with feline hemoplasmas, feline calicivirus, feline herpesvirus-1, feline coronavirus, feline leukemia and feline immunodeficiency virus, as well as Bartonella henselae and Chlamydia felis , as recently described [ 19 , 30 ]; the absence of Mhf infection was again confirmed by real-time TaqMan ® quantitative (q)PCR [ 12 ] on day 0 prior to plasma transfusion and Mhf inoculation. All donor cats and the cat from the pre-experiment were blood-typed using a commercial immunochromatography technique (Feline Lab Test A + B, Alvedia, France).…”
Section: Methodsmentioning
confidence: 99%
“…También es posible que sea transmitido a través de mordidas (Krecic et al, 2018 transplacentaria, y de forma iatrogénica por transfusión sanguínea (Aiyaranoi et al, 2018;Krecic et al, 2018;Perharić et al, 2018). Nesina et al (2015) demostraron la transmisión y el desarrollo de la infección por el ViLeF en gatos domésticos que recibieron transfusión sanguínea por parte de donadores seronegativos (sin viremia), ya que el ADN proviral de los leucocitos representa un riesgo de transmisión. Por otro lado, Vobis et al (2003) han documentado la presencia de ARN del ViLeF, hasta 24 horas postalimentación, en la pulga Ctenocephalides felis y también en sus heces.…”
Section: A Vilefunclassified